2014
DOI: 10.1264/jsme2.me14011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated Carbon Dioxide, Elevated Temperature, and Rice Growth Stage on the Community Structure of Rice Root–Associated Bacteria

Abstract: The effects of free-air carbon dioxide enrichment (FACE) and elevated soil and water temperature (warming) on the rice root–associated bacterial community were evaluated by clone library analysis of the 16S ribosomal RNA gene. Roots were sampled at the panicle initiation and ripening stages 41 and 92 days after transplanting (DAT), respectively. The relative abundances of the methanotrophs Methylosinus and Methylocystis were increased by warming and decreased by FACE at 92 DAT, which indicated that microbial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Bradyrhizobia prefer legumes (34,35) and nonlegumes (36)(37)(38) that tend to form symbiosis (39). The present study advances genomic characterization of HRS strains of soybean bradyrhizobia with abundant ISs.…”
Section: Discussionmentioning
confidence: 74%
“…Bradyrhizobia prefer legumes (34,35) and nonlegumes (36)(37)(38) that tend to form symbiosis (39). The present study advances genomic characterization of HRS strains of soybean bradyrhizobia with abundant ISs.…”
Section: Discussionmentioning
confidence: 74%
“…Root biomass and tiller number of wild rice were reported to significantly increase under elevated CO 2 (Inubushi et al, 2003;Kim et al, 2003). Accordingly, increased carbon input in the rhizosphere soil though rice root exudates and rhizodeposition was observed under elevated CO 2 (Bhattacharyya et al, 2013;Okubo et al, 2014). As microbial communities in soil can be generally mediated by carbon substrate availability, an increase in below-ground carbon input could bring changes in soil microbial biomass under climate change conditions (Rakshit et al, 2012).…”
Section: Responses Of Aoa and Aob Communities To Elevated Co 2 And Wamentioning
confidence: 99%
“…Effects had been frequently reported of CO 2 enrichment on rice ecosystem function including rice grain yield and quality, plant nutrients uptake and greenhouse gas emission (Hasegawa et al, 2013;Usui et al, 2014;Tokida et al, 2011). Correspondingly, activity and community composition of ammonia oxidizer in rice rhizosphere could be affected by elevated CO 2 through root exudates and rhizodeposition as well as soil organic carbon (Bhattacharyya et al, 2013;Okubo et al, 2014). The changes to nitrifying activity of agricultural soils under elevated atmospheric CO 2 and warming conditions had been shown to depend on soil pH, inorganic N availability, and ammonia oxidizer community structure and abundance, but these changes were difficult to correlate with those in nitrifying activity (Yao et al, 2011;Long et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous ecological studies utilizing culture-dependent and -independent analyses have been conducted to investigate these rice-associated microbes (3, 14). These studies revealed the diversity as well as functions of rice-associated microbes.…”
mentioning
confidence: 99%